1976
DOI: 10.1037/0278-7393.2.6.774
|View full text |Cite
|
Sign up to set email alerts
|

Effects of class complexity, class frequency, and preexperimental bias on rule learning.

Abstract: The difficulty of four binary conceptual rules (conjunctive, disjunctive, conditional, and biconditional) was assessed using the rule-learning paradigm in a variety of stimulus populations. Decreasing the number of unique stimuli representing each truth-table class had a facilitative effect on learning the conditional and biconditional rules. Manipulating the relative frequency of truth-table classes changed the difficulty of particular truth-table classes but had no effect on overall measures of performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…As expected, integral stimuli promote no significant facilitation. Since dimensional structure is important in disjunction, we might have expected separable stimuli to facilitate acquisition; however, as Reznick and Richman (1976) observed, many people naturally take a disjunctive approach to all rules. For these people disjunction is learned without their necessari1y learning the dimensional structure ; hence, separable stimuli would have a less facilitative effect.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As expected, integral stimuli promote no significant facilitation. Since dimensional structure is important in disjunction, we might have expected separable stimuli to facilitate acquisition; however, as Reznick and Richman (1976) observed, many people naturally take a disjunctive approach to all rules. For these people disjunction is learned without their necessari1y learning the dimensional structure ; hence, separable stimuli would have a less facilitative effect.…”
Section: Methodsmentioning
confidence: 99%
“…Past research has shown that, for these rules, certain truth-table classes are particularly difficult to learn. In the conditional, TF and FF are hardest; in the biconditional, FF is hardest (Bourne & Guy , 1968;Reznick & Richman, 1976) . For these rules, the data of this experiment show that separable stimuli, probably by heightening dimensional salience, facilitate acquisition of these difficult responses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ciborowski (21) shows that a modified biconditional rule in which ITs are "+," TFs and FTs are "-," and FFs are "other" is considerably easier than a standard biconditional problem, lending support to one of the Salatas & Bourne assumptions. But re: cent data (34,164) suggest that a majority of subjects may not enter a rule learning problem with a conjunctive bias -instead disjunctive and one-dimensional rule:; may be fa vore d. A modified model that takes account of the subject's initial bias does a better job of accounting for rule difficulty. And Dominowski & Wetherick (34) �nd that intra truth-table-class trans fer (from stimulus to stimulus) depends on the particular rule, which is difficult to account fo r within a simple bias model.…”
Section: Multidimensional Concept Learning Problemsmentioning
confidence: 95%